DSPod implementation of an MPEG-1 Layer III player with audio enhancements on two ADSP-21065L evaluation boards - Chua, Danhelson A.; Go, Allia Donna D.; Labergas, Ruben Jr. B. (2007)
MPEG-1 Layer III (MP3) algorithm is the forefront leader in digital audio compression owing to its high degree of compression without compromising quality as perceived by most listeners. Various MP3 decoding algorithms have been developed on different platforms, but only few are recognized as fully ISO compliant. The advent of decoder chips gave rise to the creation of portable stand-alone MP3 players. The continually increasing market demand for portable MP3 players that offers more exciting features has resulted in further research and development on its hardware implementation. The objective of this research is to implement an MP3 player with expanded memory on two ADSP-21065L EZ Kit Lite boards, with the basic structure of popular MP3 players as reference for its over-all functionality. Secondary objective is to apply audio enhancements to the final audio output, using a second ADSP-21065L board. The ADSP-210G5L evaluation kit has limited capabilities, particularly in handling large data input. Because of this, enhancing its interfacing flexibility and memory capacity were necessary. Audio enhancements that were implemented are 3-D sound simulation and computer-interfaced frequency equalization. A fully-functional and optimal MP3 player that is capable of enhancing its audio output is expected as the final output of this project. At the end of the project, the external memory of the ADSP-21065L Evaluation Board was successfully expanded, but the MP3 player with memory expansion failed. A highly satisfactory result, with an over-all rating of 1.98, was acquired for the frequency equalizer. 3D sound was successfully captured, with mean error around the target directionality of 30 degrees.
Thesis (B.S. E.C.E.)--University of the Philippines Diliman.
Keywords: MPEG (Video coding standard); Signal processing -- Digital techniques; Digital video; DSPod; ADSP-21065L.